Assessing and strengthening community‐based coastal governance - Mark Andrachuk; Graham Epstein; Shauna Mahajan; Zephania Arnold; Sinezio Junior; Dresy Lovasoa; Monalisa Mabandla; George W. Maina; Caroline Njeri; Samson Obiene; Geoffrey Odhiambo; Lenice Ojwang; et al. (Conservation Biology, 2026)
Community‐based coastal governance is essential for biodiversity conservation and sustainable livelihoods, yet many communities continue to face significant challenges in establishing and sustaining effective governance systems. We sought to improve understanding of the current status of community‐based coastal governance across five countries in the Southwest Indian Ocean (SWIO) region of Africa. Using the Elinor tool and data system, we examined how specific governance attributes relate to perceived social and ecological outcomes and sought insights for community‐managed areas (CMAs) in the SWIO region. Progress toward strong community‐based governance of CMAs has been uneven across the region and across governance attributes. Although some CMAs have established clearly defined management boundaries and property rights, many other CMAs are still working to improve some attributes, such as congruent regulations, transparency, accountability, and operational capacity. Perceived ecological and social outcomes correlated with different governance attributes. Perceived ecological outcomes were positively correlated with measures of property rights and local governance, whereas perceived social outcomes were correlated with local governance and operational capacity. The strength of CMA governance tended to improve in the first 5–10 years after establishment, then governance attributes plateaued or declined thereafter. These findings coincide with typical funding cycles, thus reinforcing the value of continued investment in community‐based coastal governance. Specifically, our findings point to the importance of providing long‐term capacity development and securing durable conservation finance to ensure the success of CMAs. More broadly, these findings contribute to a growing body of evidence of the importance of paying attention to when and how to leverage different types of support and capacity building.

Molecular detection of Torque teno sus virus from domestic pigs in North Central, Nigeria, 2022–2023 - Mark Samson; Daniel Geofry. ThankGod; Helen Gyang. Luka; Oluwatoyin Ruth. Morenikeji; Agnes Tinuke. Laleye; Saidu Ganih. Joel; Eche Onah. Otapka; Filibus Danjuma. Dami; Dung Davou. Pam; Nathan Yakubu. Shehu; Pam Dachung. Luka (The Veterinary Journal, 2026)

Factors associated with foot-and-mouth disease seroprevalence in small ruminants and identification of hot-spot areas in northern Nigeria - Mattia Begovoeva; David O. Ehizibolo; Adeyinka J. Adedeji; Moses O. Oguche; Olumuyiwa Oyekan; Sandra I. Ijoma; Rebecca B. Atai; Yiltawe Wungak; Banenat B. Dogonyaro; David D. Lazarus; Mark Samson; Hussaini Ularamu; et al. (Preventive Veterinary Medicine, 2023)

Comparison Between Ground, Helicopter, and Unmanned Aircraft System Magnetic Datasets: A Case Study from the Abitibi Greenstone Belt, Canada - Michael Cunningham; Claire Samson; Jeremy Laliberté; Mark Goldie; Alan Wood; David Birkett (Pure and Applied Geophysics, 2022)

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Inversion of Magnetic Data Acquired with a Rotary-Wing Unmanned Aircraft System for Gold Exploration - Michael Cunningham; Claire Samson; Jeremy Laliberté; Mark Goldie; Alan Wood; David Birkett (Pure and Applied Geophysics, 2021)

Making the Otolith Magnesium Chemical Calendar-Clock Tick: Plausible Mechanism and Empirical Evidence - Karin E. Limburg; Mark J. Wuenschel; Karin Hüssy; Yvette Heimbrand; Melvin Samson (Reviews in Fisheries Science & Aquaculture, 2018)

Quantifying the influence of geography and environment on the northeast Atlantic mackerel spawning distribution - Thomas Brunel; Cindy J. G. van Damme; Melvin Samson; Mark Dickey‐Collas (Fisheries Oceanography, 2018)
Mackerel ( Scomber scombrus ) in the northeast Atlantic have shown changes in distribution at certain times of the year, which have impacted their exploitation and management. In this study, mackerel spawning habitat over 21 recent years was characterised using generalised additive modelling, based on spatial egg density data collected every third year during targeted ichthyoplankton surveys. Mackerel spawning distribution was found to depend primarily on geographical variables (coordinates and bottom depth), with preferred spawning locations on the shelf‐edge from the north of the Iberian peninsula to the west of Scotland, with a maximum west of Ireland. Environmental drivers had a lesser influence on egg distribution. Dome shaped relationships were found with temperature and mixed layer depth, with respective optimum at 13°C and around –300 m. The model was used to reconstruct maps of the potential habitat (areas where conditions were suitable, but not necessarily used, for spawning). Little changes were observed over the years in the potential habitat, suggesting that the expansion of the egg distribution (realised habitat) was not triggered by changes in the environmental variables investigated. Little evidence was found for density‐dependent habitat selection. There was a tendency for mackerel to make more use of areas of lesser suitability in years with large stock size (1992 and 2010). This pattern, however, broke down in 2013, when stock size was the highest, as spawning occurred very south and concentrated in the most suitable habitat.

Trehalose degradation and glucose efflux precede cell ejection during germination of heat-resistant ascospores of Talaromyces macrosporus - Jan Dijksterhuis; Kenneth van Driel; Mark Sanders; Douwe Molenaar; Jos Houbraken; Rob Samson; Edwin Kets (Archives of Microbiology, 2002)